Resin films, copper-clad laminates, and circuit boards

By using a specific ratio of potassium to silicon in synthetic mica within the resin film's composition, the adhesion and dimensional stability of circuit boards are enhanced, addressing the shrinkage and adhesion issues in conventional polyarylene ether ketone resin films.

JP7617563B2Active Publication Date: 2025-01-20SHIN ETSU POLYMER CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021175747
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-27
Publication Date
2025-01-20
Estimated Expiration
2041-10-27

AI Technical Summary

Technical Problem

Conventional circuit boards using polyarylene ether ketone resin films face challenges in simultaneously improving adhesion and reducing dimensional shrinkage after etching, with the addition of talc leading to adhesion deterioration.

Method used

A molding material comprising polyarylene ether ketone resin and synthetic mica with specific potassium to silicon ratios (0.16 to 0.26) and controlled particle sizes is used to enhance adhesion and reduce dimensional shrinkage, incorporating non-swelling synthetic mica to prevent moisture-induced deterioration.

Benefits of technology

The solution improves adhesion and dimensional stability of the resin film, reducing shrinkage rates during etching and maintaining dielectric properties, while enhancing mechanical strength and preventing moisture-related degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617563000007
    Figure 0007617563000007
  • Figure 0007617563000008
    Figure 0007617563000008
  • Figure 0007617563000001
    Figure 0007617563000001
Patent Text Reader

Abstract

To provide a resin film, a copper-clad laminate, and a circuit board which can improve adhesion and reduce dimensional shrinkage.SOLUTION: A resin film 1 is formed by melting, extruding and molding a molding material containing at least a polyarylene ether ketone resin and synthetic mica, wherein a ratio of potassium to silicon in the case of measurement by an electron probe microanalyzer is within a range of 0.16-0.26. The ratio of the potassium to the silicon of the synthetic mica in the resin film 1 is within the range of 0.16-0.26, which can reduce a dimensional shrinkage ratio of the resin film 1. In addition, not natural mica but the synthetic mica excellent in adhesion to metal is used, which improves adhesion and the dimensional stability of the resin film 1, and can suppress deterioration in dielectric characteristics by moisture absorption of the resin film 1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin film, a copper-clad laminate, and a circuit board that are capable of improving dimensional stability and reducing the dimensional shrinkage rate after etching. [Background technology]

[0002] In recent years, polyarylene ether ketone (PAEK) resin, a super engineering plastic, has been attracting attention. This polyarylene ether ketone resin is a thermoplastic crystalline resin that is excellent in electrical insulation, heat resistance, chemical resistance, etc. In view of these excellent properties, polyarylene ether ketone resin is used in the automotive, energy, medical, and other fields, and is also used in the manufacture of circuit boards such as flexible printed circuit boards (FPCs) (see Patent Documents 1 and 2).

[0003] In the case of manufacturing a circuit board using such a polyarylene ether ketone resin, although not shown in the figures, a polyarylene ether ketone resin film is formed and prepared as a base substrate, copper foil that will become the circuit pattern is directly bonded to this polyarylene ether ketone resin film, and a photoresist layer for etching is laminated onto the exposed surface. Processing holes are drilled at predetermined locations of this laminated intermediate body, and the photoresist layer is exposed to ultraviolet light and developed to dissolve the photoresist layer in the unexposed areas, thereby revealing the circuit pattern.

[0004] When a polyarylene ether ketone resin film is molded, in addition to the polyarylene ether ketone resin, a fluororesin, talc, mica, or the like is added to the molding material as necessary (see Patent Document 3).

[0005] Next, the circuit pattern of the intermediate body is etched to remove the photoresist layer, the intermediate body is washed and dried, a cover film is attached to most of the intermediate body to form an insulating layer, and surface treatment such as plating is performed on exposed terminal portions, etc. After surface treatment such as plating is performed on the intermediate body in this manner, the intermediate body is externally processed, the continuity of the circuit pattern is electrically checked, and a final inspection is performed, whereby the circuit board can be manufactured. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2021-042294 A [Patent Document 2] JP 2007-051256 A [Patent Document 3] JP 2016-029164 A Summary of the Invention [Problem to be solved by the invention]

[0007] Conventional circuit boards are manufactured as described above, and although the use of a polyarylene ether ketone resin film can provide excellent electrical insulation, heat resistance, and chemical resistance, there is a problem in that it is not easy to simultaneously improve the adhesion of the polyarylene ether ketone resin film and reduce the dimensional shrinkage rate of the polyarylene ether ketone resin film after etching. If talc is blended into the molding material of the polyarylene ether ketone resin film to solve this problem, it will result in a deterioration of adhesion, even though it is possible to reduce the dimensional shrinkage rate of the polyarylene ether ketone resin film after etching of the intermediate.

[0008] The present invention has been made in view of the above, and an object of the present invention is to provide a resin film, a copper-clad laminate, and a circuit board that are capable of improving adhesion and reducing the dimensional shrinkage rate. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides a molding material containing at least polyarylene ether ketone resin and synthetic mica. The synthetic mica particles are 20% or less in diameter. And, The ratio of potassium to silicon as measured by electron probe microanalyzer is: Potassium / Silicon = 0.16~0.26 It is characterized in that the range is

[0010] In addition, the ratio of potassium to silicon measured by an electron probe microanalyzer is Potassium / Silicon = 0.21~0.26 It is preferable that the range is 100%. The molding material preferably contains at least 100 parts by mass of polyarylene ether ketone resin and 20 parts by mass or more and 80 parts by mass or less of synthetic mica. It is also preferable that the synthetic mica is a non-expanding synthetic mica.

[0011] In addition, the D95 value of the synthetic mica can be set to 35 μm or less. In addition, the specific surface area of ​​synthetic mica is 3.0 m 2 / g or more.

[0012] In addition, in order to solve the above problems, the present invention provides Claims 1 to 6 The present invention is characterized in that the resin film according to any one of claims 1 to 5 is a copper-clad laminate having a copper foil laminated and attached to at least one of the two surfaces of the resin film.

[0013] In addition, in order to solve the above problems, the present invention provides Claims 1 to 6 The present invention is characterized in that the circuit board has the resin film described in any one of 1 to 5.

[0014] Here, the resin film in the claims can be manufactured to a thickness of 2 μm or more and 1000 μm or less by a known manufacturing method such as melt extrusion molding, calendar molding, or casting. When manufacturing a resin film by melt extrusion molding, a molding material is melt-kneaded using an extrusion molding machine, and the resin film is extruded from the die of the extrusion molding machine and cooled to manufacture the resin film. In addition, the circuit board includes at least a printed wiring board, a flexible board, a high-frequency circuit board, etc.

[0015] According to the present invention, the ratio of potassium to silicon in the synthetic mica contained in the resin film is in the range of potassium / silicon = 0.16 to 0.26, so that the dimensional shrinkage rate of the resin film can be reduced. In addition, since synthetic mica is used, the adhesion and dimensional stability of the resin film can be improved, and deterioration of the dielectric properties due to moisture absorption of the resin film can be prevented. Effect of the Invention

[0016] According to the present invention, there is an effect that it is possible to improve adhesion and reduce the dimensional shrinkage rate. In addition, the amount of particles with a particle size of 1 μm or less in the total amount of synthetic mica particles is 20% or less, which contributes to reducing the dimensional shrinkage rate of the resin film after etching during the manufacture of circuit boards, and also prevents the mica from easily agglomerating.

[0017] According to the invention described in claim 2, the ratio of potassium to silicon when measured by an electron probe microanalyzer is in the range of potassium / silicon = 0.21 to 0.26, so that the strength of the base material of the resin film is improved and further improvement in adhesion can be expected. According to the invention described in claim 3, the composition contains at least 100 parts by mass of polyarylene ether ketone resin and 20 parts by mass or more and 80 parts by mass or less of synthetic mica, so that, for example, when a resin film and a copper foil are adhered to each other, the adhesion can be improved. According to the invention described in claim 4, since the synthetic mica is non-swelling, it is possible to suppress dimensional changes in the resin film caused by moisture absorption and to prevent deterioration of the dielectric properties of the resin film.

[0018] Claim 5According to this invention, the D95 value of the synthetic mica is set to 35 μm or less, so that the mechanical strength of the resin film can be expected to be improved.

[0019] Claim 6 stated According to the invention, the specific surface area of ​​synthetic mica is 3.0 m 2 / g or more, it is possible to reduce the dimensional shrinkage rate of the resin film after etching. Claim 7 or 8 According to the invention, Claims 1 to 6 Since the resin film described in any one of claims 1 to 5 is used, when a circuit board is manufactured, it is possible to achieve both improved adhesion and mechanical strength of the resin film and a reduced dimensional shrinkage rate of the resin film after etching. [Brief description of the drawings]

[0020] [Figure 1] 1 is a cross-sectional view illustrating an embodiment of a resin film and a copper-clad laminate according to the present invention. FIG. [Diagram 2] FIG. 2 is a cross-sectional explanatory view showing a schematic diagram of a second embodiment of the resin film and the copper-clad laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] A preferred embodiment of the present invention will now be described with reference to the drawings. As shown in FIG. 1, a resin film 1 in this embodiment is formed into a long strip from a molding material containing at least polyarylene ether ketone resin and synthetic mica, and is a film for copper-clad laminates 3 or circuit boards, in which the ratio of potassium to silicon in the synthetic mica is in the range of potassium / silicon = 0.16 to 0.26 when measured with an electron probe microanalyzer, and contributes to the achievement of Goal 9 of the SDGs (the United Nations' international goals for sustainable development, consisting of 17 global goals and 169 targets (achievement criteria)) adopted at the United Nations Summit.

[0022] The molding material contains at least polyarylene ether ketone (PAEK) resin and synthetic mica, and other resins and various fillers are selectively blended as necessary to form a thin resin film 1 shown in Fig. 1. This molding material contains 100 parts by mass of polyarylene ether ketone resin and 20 to 80 parts by mass of synthetic mica, preferably 100 parts by mass of polyarylene ether ketone resin and 45 to 65 parts by mass of synthetic mica.

[0023] The synthetic mica content is 20 parts by mass or more and 80 parts by mass or less because, if it is less than 20 parts by mass, the dimensional shrinkage rate of the resin film 1 after etching during the manufacture of a circuit board deteriorates and leads to a decrease in the adhesion of the resin film 1. On the other hand, if it exceeds 80 parts by mass, the adhesion of the resin film 1 decreases and the hardness of the resin film 1 increases more than necessary, making it more likely to crack.

[0024] The molding material, polyarylene ether ketone resin, is a thermoplastic crystalline resin consisting of arylene groups, ether groups, and carbonyl groups; examples of such resins include those described in Patent No. 5709878 and Patent No. 5847522, or in the literature [Asahi Research Center Co., Ltd.: PEEK, a super engineering plastic growing in cutting-edge applications (Part 1)], and has a melting point of 300°C to 400°C and is excellent in electrical insulation, mechanical properties, heat resistance, chemical resistance, radiation resistance, hydrolysis resistance, low water absorption, recyclability, etc.

[0025] Specific examples of polyarylene ether ketone resins include polyether ether ketone (PEEK) resin, polyether ketone ketone (PEKK) resin, polyether ketone (PEK) resin, polyether ketone ether ketone ketone (PEKEKK) resin, etc. Among these, polyether ether ketone resin is the most suitable because it can obtain an optimal processing temperature for manufacturing the copper-clad laminate 3 and the circuit board and is inexpensively available.

[0026] Examples of polyether ether ketone resin products include Victrex Powder series and Victrex Granules series, Daicel-Evonik VestaKeep series, and Solvay Specialty Polymers KetaSpire PEEK series. Examples of polyether ketone ketone resin products include Arkema KEPSTAN series. Examples of polyether ketone resin products include Victrex HT G22 and HT G45. Examples of polyether ketone ether ketone ketone resin products include Victrex ST G45.

[0027] The polyarylene ether ketone resin may be used alone or in a mixture of two or more kinds, or may be a copolymer. The polyarylene ether ketone resin is usually used in a form suitable for molding, such as powder, granules, or pellets. The method for producing the polyarylene ether ketone resin is not particularly limited, but for example, the method described in the literature [Asahi Research Center Co., Ltd.: Super engineering plastic PEEK growing in cutting-edge applications (Part 1)] is used.

[0028] The synthetic mica used as the molding material is fluorine tetrasilicic mica, fluorine phlogopite, or the like, whose main components are fluorine (F), magnesium (Mg), silicon (Si), and potassium (K), and functions to suppress deterioration of dielectric properties due to moisture absorption and contribute to the adhesion and dimensional stability of the resin film 1. This synthetic mica is classified into non-swelling, swelling, lipophilic, etc., but non-swelling mica is preferred, as it suppresses dimensional changes and deterioration of dielectric properties of the resin film 1 due to moisture absorption and is also excellent in heat resistance.

[0029] Synthetic mica is composed of many mica particles of different particle sizes, with the amount of mica particles with a particle size of 1 μm or more, for example, an average particle size of 3.4 μm to 13 μm, being 80% or more of the total, and the amount of mica particles with a particle size of 1 μm or less being 20% ​​or less of the total, preferably 0.1% to 20%, more preferably 0.15% to 10%. This is because if the amount of mica particles with a particle size of 1 μm or less exceeds 20% of the total mica particles, it is not possible to reduce the dimensional shrinkage rate of the resin film 1 after etching during the manufacture of the circuit board, and the mica particles are more likely to aggregate.

[0030] The specific surface area of ​​the synthetic mica is 3.0 m2 in order to reduce the dimensional shrinkage rate of the resin film 1 after etching during the manufacture of the circuit board. 2 / g or more, preferably 3.0m 2 / g or more 15m 2 / g or less, more preferably 3.5m 2 / g or more 15m 2 / g or less, more preferably 3.5m 2 / g or more 9.71m 2 / g or less. The specific surface area of ​​synthetic mica is 3.0m 2 / g or more because the specific surface area of ​​synthetic mica is 3.0 m 2 If the specific surface area is less than 1 / g, the mica particles will contain a large amount of aggregates or coarse particles. The specific surface area of ​​the mica particles can be measured by a permeation method or various gas adsorption methods, but it is preferable to measure it in accordance with JIS Z 8830:2013.

[0031] The median diameter D50 of the synthetic mica is preferably 2.0 μm or more and 10 μm or less. The reason for selecting the median diameter (central diameter) rather than the average diameter or the most frequent diameter is that it is suitable for grasping a representative value of the particle size distribution of the mica particles and is convenient when comparing the particle size distribution of multiple samples. In order to improve the film formability of the resin film 1, the median diameter D50 of the synthetic mica is optimally 2.0 μm or more and 10 μm or less, preferably 2.0 μm or more and 6.0 μm or less, and more preferably 2.8 μm or more and 5.10 μm or less.

[0032] The D95 value of the synthetic mica is optimally 35 μm or less, preferably 6.00 μm or more and 35 μm or less, and more preferably 6.00 μm or more and 16 μm or less, from the viewpoint of improving the mechanical strength of the resin film 1. A specific example of such a synthetic mica product is the Micromica MK series (product name: manufactured by Katakura Co-op Agri Co., Ltd.).

[0033] In addition to the above resins and synthetic mica, various fillers can be added to the molding material within the range that does not impair the characteristics of the present invention. For example, silica, boron nitride (BN), calcium carbonate, antioxidants, light stabilizers, ultraviolet absorbers, plasticizers, lubricants, flame retardants, antistatic agents, heat resistance improvers, inorganic compounds, organic compounds, etc. can be selectively added.

[0034] The resin film 1 is formed from such a molding material, and the molding method may be any of melt extrusion, calendar molding, casting, etc. However, in consideration of handling and simplification of manufacturing equipment, the melt extrusion is optimal. When manufacturing the resin film 1 by this melt extrusion, the molding material is melt-kneaded using an extrusion molding machine, and the resin film 1 is continuously extruded from a T-die of the extrusion molding machine and cooled, whereby a thin resin film 1 can be manufactured.

[0035] In the above, when the resin film 1 is manufactured, first, the prepared molding material is charged into the raw material inlet of the melt extruder, preferably while supplying an inert gas, and the molding material is melt-kneaded in the melt extruder heated to a temperature below the thermal decomposition temperature. From the viewpoint of dispersibility and workability, the molding material is preferably prepared by adding synthetic mica to molten polyarylene ether ketone and melt-kneading them. The melt extruder is not particularly limited, but for example, a single screw extruder, a twin screw extruder, a triple screw extruder, etc. are used.

[0036] After the molding material is melt-kneaded in a melt extrusion molding machine, a strip-shaped resin film 1 is continuously extruded from a T-die at the tip of the melt extrusion molding machine, and this resin film 1 is sequentially wound around multiple cooling rolls, a pair of pressure rolls, a tension roll, and a winding core of a winding machine, and is cooled by sliding it against the multiple cooling rolls. After the two side portions of the resin film 1 are cut with a slit blade to adjust the appearance, the resin film 1 is sequentially wound around the winding core of the winding machine to form a raw sheet of resin film 1, and the resin film 1 can be manufactured.

[0037] The thickness of the produced resin film 1 is not particularly limited, but considering the strength, rigidity, productivity, and versatility as a base for a circuit board, it is optimally 2 μm to 1000 μm, preferably 10 μm to 250 μm, and more preferably 50 μm to 100 μm. The thickness of this resin film 1 can be measured using a dedicated micrometer or the like.

[0038] The ratio of potassium (K) to silicon (Si) among the main components of the synthetic mica in the produced resin film 1 is preferably in the range of K / Si=0.16 to 0.26, preferably 0.21 to 0.26, and more preferably 0.21 to 0.24, when measured by an electron probe microanalyzer (EPMA). Examples of the electron probe microanalyzer include the EPMA-1720 Series (manufactured by Shimadzu Corporation: product name) and JXA-8100 (manufactured by JEOL Ltd.: product name).

[0039] From the experimental results, the maximum tensile strength of the produced resin film 1 was 50N / mm 2 More than 50N / mm 2 More than 120N / mm 2 Less than or equal to 80N / mm 2 More than 120N / mm 2 The following is preferable: The tensile strength of this resin film 1 can be measured in accordance with, for example, JIS K 7127:1999.

[0040] From experimental results, the dielectric loss tangent of the produced resin film 1 at a frequency of about 28 GHz is preferably 0.0040 to 0.0051, and more preferably 0.0043 to 0.0051. The dielectric loss tangent of this resin film 1 is not particularly limited, but can be measured by the Fabry-Perot method using an open interferometer, a method for determining the relative dielectric constant and dielectric loss tangent at high frequencies by a cavity resonator perturbation method, a three-terminal measurement method using a mutual induction bridge circuit, or the like. Of these, the Fabry-Perot method or the cavity resonator perturbation method, which have excellent high resolution, are optimal.

[0041] Next, when manufacturing the copper-clad laminate 3 using the resin film 1, the resin film 1 having the above-mentioned characteristics and the copper foil 2 are prepared, and these resin film 1 and the copper foil 2 are directly laminated together. The thickness range of the copper foil 2 is specified to be 2 μm or more and 100 μm or less, preferably 10 μm or more and 50 μm or less, because if the thickness is less than 2 μm, it is difficult to handle during manufacturing and use, and if it exceeds 100 μm, it takes a long time to manufacture.

[0042] The laminated surface of the copper foil 2 may be either the front or back surface of the copper foil 2. When the copper foil 2 is an electrolytic copper foil produced by an electrolytic manufacturing apparatus, the electrolytic copper foil has a shiny (S) surface that is smooth and glossy on the drum-shaped cathode side and a matte (M) surface on the opposite side of the shiny surface, and either the shiny surface or the matte surface can be used as the laminated surface. Examples of such copper foil 2 products include TQ-M7-VSP (product name manufactured by Mitsui Mining & Smelting Co., Ltd.), 3EC-III (product name manufactured by Mitsui Mining & Smelting Co., Ltd.), and CF-T49A-DS-HD2-12 (product name manufactured by Fukuda Metal Foil & Powder Co., Ltd.).

[0043] Although it is not necessary to perform any particular treatment on the opposing surfaces of the resin film 1 and the copper foil 2, at least one of the opposing surfaces may be selectively subjected to a corona treatment, a plasma treatment, or an ultraviolet treatment. By performing such treatment, it is possible to improve the strength, adhesiveness, and cleanability.

[0044] After the resin film 1 and the copper foil 2 are laminated, they are sandwiched in a hot press or between rolls and heated and pressurized to thermocompression bond them, thereby producing a copper-clad laminate 3 in which the resin film 1 and the copper foil 2 are integrated. The optimum temperature for thermocompression bonding in this case is between the melting point of the resin film 1 -20°C and +20°C, preferably between the melting point of the resin film 1 -20°C and +10°C.

[0045] The melting point of the resin film 1 varies depending on the presence or absence of filler in the molding material, but for example, when it is 340°C, the temperature range for thermocompression bonding is set to 320°C or more and 360°C or less. This is because when it is less than the melting point of the resin film 1 -20°C, the polyarylene ether ketone resin on the opposing surface does not melt. Also, when it exceeds 360°C, the fluidity of the molding material increases, so the thickness of the resin film 1 is likely to vary, and the thickness precision of the copper-clad laminate 3 deteriorates.

[0046] The shrinkage rate of the resin film 1 in the copper-clad laminate 3 is less than 0.30%, preferably 0.08% to 0.28%, when measured under conditions of 150°C x 30 min in accordance with JIS C 6481:1996. In addition, the adhesion strength of the resin film 1 in the copper-clad laminate 3, in other words, the peel strength, is 5.0 N / cm or more, preferably 7.0 N / cm or more, more preferably 7.5 N / cm or more, when measured in accordance with JIS Z 0237:2009 (Test method for adhesive tapes and adhesive sheets) in order to ensure practical use and reliability. The upper limit of the adhesion strength is not particularly limited, but generally 15 N / cm or less is preferable.

[0047] Next, when manufacturing a circuit board such as a flexible board using the copper-clad laminate 3, a photoresist layer for etching is laminated onto the exposed surface of the copper foil 2 of the copper-clad laminate 3, processing holes are drilled at predetermined locations in this laminated intermediate, and the photoresist layer is exposed to ultraviolet light and developed to dissolve the photoresist layer in the unexposed areas, revealing the circuit pattern.

[0048] Next, the circuit pattern of the intermediate is etched to remove the photoresist layer, the intermediate is washed and dried, a cover film is attached to most of the intermediate to form an insulating layer, and exposed terminal parts and the like are subjected to surface treatment such as plating. The shrinkage rate of the resin film 1 after etching is less than 0.30%, and preferably 0.04% to 0.27%, optimally, when measured in accordance with JIS C 6481:1996. After the intermediate is thus subjected to surface treatment such as plating, the intermediate is externally machined, the continuity of the circuit pattern is electrically checked, and a final inspection is carried out to manufacture the circuit board.

[0049] According to the above, when the potassium to silicon ratio of the synthetic mica of the resin film 1 is in the range of potassium / silicon = 0.16 to 0.26, the dimensional shrinkage rate of the resin film 1 can be reduced, and therefore the dimensional shrinkage rate of the resin film 1 after etching or heating at 150°C can be reduced.

[0050] To explain the ratio and effect in detail, since the crystal structure of synthetic mica has a structure in which potassium (K) is contained between the crystal layers, it is considered that the lower the ratio of potassium, the thinner the synthetic mica particles. Therefore, for example, the smaller the ratio of potassium, the greater the number of particles in 1 g of synthetic mica. It is presumed that when the number of synthetic mica particles exceeds a certain level, it becomes difficult to form a uniform dispersion distribution structure in the polyarylene ether ketone resin. From the above, it is presumed that in the case of a resin film 1 with K / Si less than 0.16, the dispersion distribution in the polyarylene ether ketone resin deteriorates, and therefore the effect of reducing the heat shrinkage rate at 150°C is reduced.

[0051] In contrast, in the case of resin film 1 with K / Si exceeding 0.26, although it has excellent dispersibility in the polyarylene ether ketone resin, it is presumed that the amount of potassium contained in the synthetic mica crystal structure is large and the thickness of the mica particles is large, so that the contribution rate of the resin film 1 to the effect of reducing the shrinkage rate in the planar direction is slightly replaced by the contribution rate in the thickness direction. In other words, it is presumed that the shrinkage rate in the planar direction of the resin film 1 when heated is large.

[0052] When the ratio of the proportions of potassium and silicon is limited to a narrow range of potassium / silicon = 0.21 to 0.26, it is possible to reduce the dimensional shrinkage rate of the resin film 1, further improve the strength of the base material of the resin film 1, and significantly improve the adhesion. Furthermore, since synthetic mica, which has excellent adhesion to metals, is used instead of natural mica, it is possible to improve the adhesion and dimensional stability of the resin film 1 and suppress deterioration of the dielectric properties of the resin film 1 due to moisture absorption.

[0053] 2 shows a second embodiment of the present invention, in which copper foils 2 are directly laminated on both sides of a resin film 1, and then the laminate is sandwiched in a hot press or between rolls and heated and pressed to thermocompress, thereby producing a copper-clad laminate 3 in which the resin film 1 and the pair of copper foils 2 are integrated. The rest of the structure is similar to the above embodiment, so a description thereof will be omitted.

[0054] The present embodiment is expected to provide the same advantageous effects as the above-described embodiment, and it is clear that the present embodiment can be of great use in the manufacture of double-sided circuit boards in which complex circuits can be formed by crossing wiring.

[0055] In the above embodiment, the resin film 1 is used for a circuit board, but the present invention is not limited to this. For example, the resin film 1 may be used for other purposes such as audio equipment. EXAMPLES

[0056] Examples of the resin film and the copper-clad laminate according to the present invention will be described below together with comparative examples. Polyarylene ether ketone resin and seven types of synthetic mica were prepared to manufacture the resin films used in Examples 1 to 8 and Comparative Examples 1 to 3. As the polyarylene ether ketone resin, a polyether ether ketone (PEEK) resin having a melting point of 341°C and a glass transition temperature of 147°C (manufactured by Victrex: product name Victrex Granules series 450G) or a polyether ketone ketone (PEKK) resin having a melting point of 360°C and a glass transition temperature of 165°C (manufactured by Arkema: product name KEPSTAN series 8002) was used (see Table 4).

[0057] The seven types of synthetic mica were analyzed for the elements contained in them using an X-ray fluorescence analyzer (Shimadzu Corporation: product name EDX-8000). Specifically, the synthetic mica powder was evacuated inside the analyzer, and then qualitative and quantitative analysis was performed with the measurement mode set to metal oxides. The quantitative results of the obtained metal oxides, etc. were then converted into ratios of metal elements, etc., and the results are shown in Table 2.

[0058] For example, when synthetic mica 1 was analyzed, SiO 2 (55.3%), MgO(26.5%), K 2 O(8.5%), CaO(0.29%), Fe 2 O 3 (0.17%), Al 2 O 3 The ratio of each metal element and F was calculated based on the molecular weight and atomic weight of the metal oxides and F listed below, and is summarized in Table 2.

[0059] Molecular weight and atomic weight of metal oxides and F SiO 2 :60.1 MgO: 40.3 K 2 O:94.2 CaO: 56.1 Fe2 O 3 :159.7 Al 2 O 3 :102.0 F:19.0

[0060] ·Calculation example SiO 2 In the case of 55.3 (SiO 2 Ratio of SiO 2 (molecular weight of) = 0.920. In the case of MgO, the formula is 26.5 (the ratio of MgO determined by X-ray fluorescence analysis) ÷ 40.3 (the molecular weight of MgO) = 0.657. K 2 In the case of O, 8.5 (K by X-ray fluorescence analysis) 2 O ratio)÷94.2(K 2 Molecular weight of O) × 2 = 0.18. Similar calculations were performed for other metal oxides and F. The results were calculated from the results of X-ray fluorescence analysis of each synthetic mica particle and are summarized in Table 2.

[0061] The seven types of synthetic mica were: synthetic mica 1 for comparison: MK-100DS (product name, manufactured by Katakura Co-op Agri Co., Ltd.) with K / Si = 0.78; synthetic mica 2: MK-PDS (product name, manufactured by Katakura Co-op Agri Co., Ltd.) with K / Si = 0.67; synthetic mica 3: MK-PGDS (product name, manufactured by Katakura Co-op Agri Co., Ltd.) with K / Si = 0.66; synthetic mica 4: FGMK80DS (product name, manufactured by Katakura Co-op Agri Co., Ltd.) with K / Si = 0.73; The synthetic mica 1 was MK100PG / 60-0 with K / Si = 0.56 (manufactured by Katakura Coop Agri Co., Ltd.: product name), synthetic mica 5 was MK100PG / 60-0 with K / Si = 0.56 (manufactured by Katakura Coop Agri Co., Ltd.: product name), synthetic mica 6 was MK100PG / 60-6 with K / Si = 0.55 (manufactured by Katakura Coop Agri Co., Ltd.: product name), and for comparison synthetic mica 7 was MK100PG / 40-6 with K / Si = 0.37 (manufactured by Katakura Coop Agri Co., Ltd.: product name) (see Table 1).

[0062] The elemental ratios of each synthetic mica were detected by X-ray fluorescence analysis, and are shown in Table 2. The results of converting the data in Table 2 are shown in Table 3. Examples of the calculation formulas in Table 3 are (Mg ratio)÷(Si ratio)×4=0.657÷0.920×4=2.86, and (K ratio)÷(Si ratio)×4=0.180÷0.920×4=0.78.

[0063] The particle size distribution of the synthetic mica was measured in accordance with JIS Z 8825:2013. Water was used as the dispersion liquid for this measurement, and the volume distribution was evaluated by laser diffraction / scattering using a particle size distribution measuring device (manufactured by Microtrack Bell Corporation: product name: MT3300EXII), and the results are summarized in Table 1. The specific surface area of ​​the synthetic mica was also measured in accordance with JIS Z 8830:2013.

[0064] [Table 1]

[0065] [Table 2]

[0066] [Table 3]

[0067] Example 1 First, a resin film having a thickness of 100 μm was melt-extruded from a molding material containing polyether ether ketone resin and synthetic mica 2. As shown in Table 4, the mass of the molding material was 100 parts by mass of polyether ether ketone resin and 45 parts by mass of synthetic mica 2.

[0068] After the resin film was melt-extruded, the ratio of the constituent elements of this resin film was measured using an electron probe microanalyzer (EPMA) (product name: JXA-8100) manufactured by JEOL Ltd. under the conditions of an acceleration voltage of 15 kV, an irradiation diameter of φ100 μm, and an irradiation current of 50 nA. A gold deposition layer of approximately 150 nm was formed on the surface of the resin film using a vacuum deposition device to prepare a measurement sample. In addition, measurements using the EPMA were performed at three randomly selected positions on the measurement sample, and the average of the results of the three measurements was calculated. From the measurement results, elements such as C, O, F, Mg, Si, K, and Ca were mainly detected, and the atomic percentages of F, Mg, Si, K, and Ca are listed in Tables 5 and 6.

[0069] Next, the resin film and the prepared copper foil were cut to 320mm x 320mm, laminated directly, sandwiched between 1mm thick SUS plates, and thermocompressed for 5 minutes at a surface pressure of 4MPa in a heat press machine with a hot plate set to 350℃, before being removed to produce a two-layer copper-clad laminate. The copper foil used was 12μm thick TQ-M7VSP (product name: manufactured by Mitsui Mining & Smelting Co., Ltd.).

[0070] After preparing a two-layered copper-clad laminate, the shrinkage of the resin film of the copper-clad laminate after etching, the shrinkage after treatment under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, and are shown in Table 5. The shrinkage of the resin film after etching and after treatment under conditions of 150°C x 30 min was measured in accordance with JIS C 6481:1996. Specifically, the copper-clad laminate was cut to 300 x 300 mm, punch holes were made at four ends, and the distance between the punch holes was measured in the extrusion direction and the width direction, and the measured distance was used as a reference to measure the same punch hole positions after etching and after 150°C x 30 min, and the shrinkage was calculated from the dimensional change.

[0071] - Shrinkage rate of resin film after etching The laminated copper foil was dissolved in an aqueous solution of iron chloride to prepare a resin film as a test specimen, and measurements were made in the extrusion direction and width direction of the resin film. A two-dimensional length measuring machine (product name: VMH600, manufactured by Mino Group Co., Ltd.) was used to measure the dimensions.

[0072] Shrinkage rate under conditions of 150℃×30min Next, measurements were made in the extrusion direction and width direction of the resin film under conditions of 150°C x 30 min. Specifically, after processing in a hot air circulating thermostatic chamber for a specified time and temperature, the resin film was cooled to room temperature, and the length of the resin film was measured for the same part previously measured. A two-dimensional length measuring machine (product name: VMH600, manufactured by Mino Group Co., Ltd.) was used to measure the dimensions. The target shrinkage rate of the resin film after 150°C was set to less than 0.30%.

[0073] Adhesion of copper-clad laminates The adhesion of the copper-clad laminate was measured by cutting the copper-clad laminate into a 25 mm wide specimen, and measuring the peel strength (adhesion) when the copper foil was pulled from the copper-clad laminate at a peel speed of 0.3 mm / min and a peel angle of 180°, while the copper-clad laminate was fixed to a support and the copper foil was fixed to a pulling jig, according to JIS Z0237:2009. Adhesion was evaluated as ◯ for 7 N / cm or more, △ for 5 N / cm or more, and × for less than 5 N / cm.

[0074] ·Ultimate tensile strength of copper clad laminate The maximum tensile strength of the resin film in the copper-clad laminate was evaluated as the maximum tensile strength at 23°C. The tensile strength was measured in the extrusion direction and width direction (perpendicular to the extrusion direction) of the resin film. The measurement was performed in accordance with JIS K7127, at a pulling speed of 50 mm / min and a temperature of 23°C. The measured maximum tensile strength was 80 Nmm 2 Above 50Nmm 2 The above was evaluated as △.

[0075] ·Dielectric tangent of copper clad laminate The dielectric tangent of the copper-clad laminate was measured using an electronic measuring instrument (product name: Compact USB Vector Network Analyzer MS46122B, manufactured by Anritsu) using the Fabry-Perot method, a type of open resonator method, at a frequency of around 28 GHz, when dry and after 24 hours of immersion in water.

[0076] Specifically, the resin film removed by dissolving the copper foil in an aqueous iron chloride solution was cut into 100 x 100 mm pieces, and the cut test pieces were left in a constant temperature and humidity room at 23 ± 2°C and 50 ± 10% RH for more than 10 hours, after which the values ​​measured using the Fabry-Perot method were used as the dielectric tangents before immersion in water. For measurements 24 hours after immersion in water, the test pieces whose dielectric properties were measured before immersion were immersed in ion-exchanged water for 24 hours, then removed and the water adhering to the surface of the copper-clad laminate was wiped off with paper. After that, the test pieces were left in an environment of 23 ± 2°C and 50 ± 10% RH for 5 minutes, and then measured using the Fabry-Perot method. All measurements before immersion at 50% RH and after 24 hours of immersion were performed in an environment of 23 ± 2°C and 50 ± 10% RH.

[0077] The resonator used was an open-type resonator (product name: Fabry-Perot resonator Model No. DPS03, manufactured by Keycom). For the measurement, a copper-clad laminate was placed on the sample stage of the open-type resonator fixture, and a vector network analyzer was used to measure the Fabry-Perot method, which is a type of open-type resonator method. Specifically, the dielectric loss tangent was measured by a resonance method that utilizes the difference in resonance frequency between a state in which the copper-clad laminate was not placed on the sample stage and a state in which the copper-clad laminate was placed on the sample stage. The specific frequency used for the measurement was 28 GHz. The target value for the dielectric loss tangent tanδ after 24 hours of water immersion was less than 0.0080, and a good value was 0.0075 or less.

[0078] Example 2 The procedure was basically the same as in Example 1, but the amount of polyether ether ketone resin was changed to 100 parts by mass, and the amount of synthetic mica 3 was changed to 45 parts by mass. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0079] Example 3 The procedure was basically the same as in Example 1, but the amount of polyether ether ketone resin was changed to 100 parts by mass, and the amount of synthetic mica 3 was changed to 45 parts by mass. Also, a resin film having a thickness of 50 μm was melt extrusion molded instead of a thickness of 100 μm. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0080] Example 4 Basically, it was the same as Example 1, but the amount of polyether ketone ketone resin was changed to 100 parts by mass and the amount of synthetic mica 3 was changed to 45 parts by mass. In addition, after the resin film was melt-extruded, this resin film and the prepared copper foil were cut to 320 mm x 320 mm, and directly laminated, and these were sandwiched between 1 mm thick SUS plates, and heat-pressed for 5 minutes at a surface pressure of 4 MPa using a heat press machine with a hot plate set to 370 ° C., and then removed to produce a two-layer copper-clad laminate. The copper foil used was TQ-M7VSP [product name: manufactured by Mitsui Mining & Smelting Co., Ltd.] with a thickness of 12 μm.

[0081] The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0082] Example 5 The procedure was basically the same as in Example 1, but the amount of polyether ether ketone resin was changed to 100 parts by mass, and the amount of synthetic mica 3 was changed to 65 parts by mass. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0083] Example 6 The procedure was basically the same as in Example 1, but the amount of polyether ether ketone resin was changed to 100 parts by mass, and the amount of synthetic mica 6 was changed to 45 parts by mass. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0084] Example 7 The procedure was basically the same as in Example 1, but the amount of polyether ether ketone resin was changed to 100 parts by mass, and the amount of synthetic mica 5 was changed to 45 parts by mass. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0085] Example 8 The procedure was basically the same as in Example 1, but the amount of polyether ether ketone resin was changed to 100 parts by mass, and the amount of synthetic mica 3 was changed to 85 parts by mass. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 5.

[0086] Comparative Example 1 Basically, the procedure was the same as in Example 1, but a resin film having a thickness of 100 μm was melt extrusion molded from a molding material containing polyether ether ketone resin and synthetic mica 1. As shown in Table 4, the mass of the molding material was 100 parts by mass of polyether ether ketone resin and 45 parts by mass of synthetic mica 1. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 6.

[0087] Comparative Example 2 Basically, the process was the same as in Example 1, but a resin film having a thickness of 100 μm was melt extrusion molded from a molding material containing polyether ether ketone resin and synthetic mica 7. As shown in Table 4, the mass of the molding material was 100 parts by mass of polyether ether ketone resin and 45 parts by mass of synthetic mica 7. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 6.

[0088] Comparative Example 3 Basically, the procedure was the same as in Example 1, but a resin film having a thickness of 100 μm was melt extrusion molded from a molding material containing polyether ether ketone resin and synthetic mica 4. As shown in Table 4, the mass of the molding material was 100 parts by mass of polyether ether ketone resin and 45 parts by mass of synthetic mica 4. The shrinkage rate after etching of the resin film of the dried copper-clad laminate, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of about 28 GHz were measured and evaluated, as shown in Table 6.

[0089] [Table 4]

[0090] [Table 5]

[0091] [Table 6]

[0092] 〔evaluation〕 In the case of Examples 1 to 7, the potassium to silicon ratio of the synthetic mica of the resin film was within the range of K / Si = 0.16 to 0.26, so excellent results were obtained with respect to the shrinkage rate after etching of the resin film, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of around 28 GHz.

[0093] In the case of Example 8, excellent results were obtained with respect to the shrinkage rate after etching of the resin film, the shrinkage rate under the condition of 150°C x 30 min, the maximum tensile strength, and the dielectric loss tangent at a frequency of about 28 GHz, but since the synthetic mica 3 was changed to 85 parts by mass, the adhesion decreased, regardless of practicality. Therefore, the synthetic mica is optimally used in an amount of 20 parts by mass or more and 80 parts by mass or less.

[0094] In contrast, in the case of each comparative example, the potassium to silicon ratio of the synthetic mica in the resin film was outside the range of K / Si = 0.16 to 0.26, so problems arose with respect to the shrinkage rate after etching of the resin film, the shrinkage rate under conditions of 150°C x 30 min, adhesion, maximum tensile strength, and dielectric tangent at a frequency of around 28 GHz. [Industrial Applicability]

[0095] The resin film, copper-clad laminate, and circuit board according to the present invention are used in fields such as information and communications and automotive equipment. [Explanation of symbols]

[0096] 1 Resin film 2 Copper foil 3 Copper-clad laminate

Claims

1. A resin film molded from a molding material containing at least a polyarylene ether ketone resin and synthetic mica, in which the amount of particles having a particle diameter of 1 μm or less among all the particles of the synthetic mica is 20% or less, The ratio of potassium to silicon as measured by electron probe microanalyzer is: Potassium / silicon = 0.16 to 0.26 A resin film characterized in that

2. The ratio of potassium to silicon as measured by electron probe microanalyzer is: Potassium / silicon = 0.21 to 0.26 The resin film according to claim 1, wherein the thickness of the resin film is within the range of 100 nm to 150 nm.

3. 3. The resin film according to claim 1, wherein the molding material contains at least 100 parts by mass of polyarylene ether ketone resin and 20 parts by mass or more and 80 parts by mass or less of synthetic mica.

4. 4. The resin film according to claim 1, 2 or 3, wherein the synthetic mica is non-expandable synthetic mica.

5. 5. The resin film according to claim 1, wherein the synthetic mica has a D95 value of 35 μm or less.

6. The specific surface area of ​​synthetic mica is 3.0 m 2 The resin film according to claim 1 , wherein the viscosity is 1 / g or more.

7. A copper-clad laminate, characterized in that copper foil is laminated and attached to at least one of the two sides of a resin film described in any one of claims 1 to 6.

8. A circuit board having a resin film described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Resin composition

    JP2004176032A

  • JP2007‐051256A

  • JP2016‐029164A

  • JP2021‐042294A

  • Resin film, conductive laminate, and circuit board

    JP2023050376A